Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Seasonal dynamics of microbial communities link to summer-autumn aquaculture disease outbreaks in Sanggou Bay - Longfei Lu; Lingfang Ni; Chunxiang Ai; Dongdong Zhang; Pengfei Zheng; Xuejing Li; Xin Liu; Hongyue Dang (Frontiers in Marine Science, 2025)
Marine microorganisms play a vital role in aquaculture by influencing water quality and the health of cultured species. Relative to conventional mono-species aquaculture, integrated multi-trophic aquaculture is more environmentally friendly and economically sustainable. However, the temporospatial dynamics of the microbial community in different aquaculture modes and their roles in the seasonal diseases of aquacultural organisms are largely unknown. Here, the seawater bacterial communities and potential pathogens were investigated over thirteen months in three different aquaculture types in Sanggou Bay, a typical maricultural area with nearly 60 years of history. Seasonality played a primary role, while aquaculture type played a subtle role in shaping the bacterioplankton community. Diverse potential pathogens were identified, and r -strategist bacteria, most of which were opportunistic pathogens and typified by Vibrio species, increased and dominated in late summer and autumn, a period of high-risk disease outbreaks in mariculture organisms. Network analyses indicated that the increase in r -strategist bacteria reduced the complexity of microbial interactions, and Vibrio halioticoli (OTU1389), a hub species with extensive positive correlations to other Vibrio OTUs, likely contributed to the increase of pathogenic vibrios due to its macroalgae degradation capability. The major potential pathogenic Vibrio OTUs were further corroborated by genome analyses and environmental simulation experiments using pathogenic Vibrio isolates, including two new species. Moreover, we found seawater dissolved oxygen, temperature, and transparency correlated significantly with the bacterioplankton temporospatial dynamics and the seasonal outbreaks of bacterial pathogens. Our results emphasize the necessity of synchronically monitoring the bacterial community, its pathogens-stimulating species, such as V. halioticoli and other macroalgae-degrading bacteria, and critical physicochemical parameters for predicting and preventing pathogen outbreaks in mariculture.

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Binding properties of olfactory proteins to host volatiles, free fatty acids and cuticular hydrocarbons in the termite Reticulitermes aculabialis - Wenxu Yang; Chenxu Ye; Lu Wang; Jinjuan Nie; Xinyi Liu; Tiange Zhang; Wenxiu Zhang; Noor us Saba; Lingfang Yin; Lianxi Xing; Xiaohong Su (Insect Biochemistry and Molecular Biology, 2025)

Utilizing the immanent chloride ions in wastewater for reactive chlorine species photogeneration towards effective ammonia nitrogen removal - Zhaofen Xu; Lingfang Tang; Yuanyi Zhou; Gang Lu; Haojie Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

Isolation and evaluation of strong endogenous promoters for the heterologous expression of proteins in Pichia pastoris - Yafei Zhang; Shengyan Wang; Lingfang Lu; Chenshan Zhang; Fan Cai; Yao Lin; Yide Huang (World Journal of Microbiology and Biotechnology, 2022)